FENOMENA KEPANIKAN MASKULIN DIBALIK PROGRAM KONTRASEPSI LAKI-LAKI - Yola Ninda Dwi Woro Dyah Sehnur (LPPM Universitas Negeri Surabaya, 2024)
Family planning is a program that is stigmatized as a woman's responsibility. However, with the increasing number of family planning failures in various regions, the government through the BKKBN has introduced contraception that can be used by men. Male contraceptive options so far include condoms and vasectomies. In recent years, the government has accelerated the increase in male birth control acceptors through various methods, one of which is by subsidizing vasectomy costs and receiving prizes. But unfortunately, these efforts have not resulted in significant improvements. This research focuses on the reasons why men's participation as family planning acceptors is still low even though various methods have been implemented. The cause is referred to in this article as 'masculine panic'. This research is an exploration of conceptualization based on revealing courageous news to uncover masculine fears. It is hoped that this concept exploration will be able to provide an alternative and in-depth explanation of the various technical strategy failures that have been implemented by the government. Keywords: Masculine Panic; Family Planning; Male Contraception; Vasectomy; BKKBN